1992
DOI: 10.1520/jfs13314j
|View full text |Cite
|
Sign up to set email alerts
|

ABO Genotyping by Polymerase Chain Reaction

Abstract: ABO blood group system's genotyping by polymerase chain reaction in genomic DNA level is developed. The positions of nucleotide 258 and 700 of cDNA from A transferase were used to distinguish A, B, and O alleles by restriction enzyme digestion. To identify the 258th nucleotide, a 199- or 200-bp DNA fragment was amplified by PCR and digested with Kpn I. For the 700th nucleotide, a 128-bp PCR amplified fragment was designed and digested with Alu I. By examining the DNA fragment digested patterns, ABO genotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 16 publications
1
60
0
3
Order By: Relevance
“…There are several polymerase chain reaction (PCR) based methods used to identify the ABO genotypes, such as PCR followed by restriction digestion [3,4], denaturing gradient gel electrophoresis [5], single-strand conformation polymorphism [6], and allele-specific PCR [7,8]. Although PCR is technically simple, it is labor-intensive and time-consuming.…”
Section: Dna 정제 없이 전혈을 사용한 빠른 Abo 유전형 검사mentioning
confidence: 99%
“…There are several polymerase chain reaction (PCR) based methods used to identify the ABO genotypes, such as PCR followed by restriction digestion [3,4], denaturing gradient gel electrophoresis [5], single-strand conformation polymorphism [6], and allele-specific PCR [7,8]. Although PCR is technically simple, it is labor-intensive and time-consuming.…”
Section: Dna 정제 없이 전혈을 사용한 빠른 Abo 유전형 검사mentioning
confidence: 99%
“…9 Two primer pairs were designed to distinguish between A and O alleles (Table 1A). 10 The primer pairs were redundant and were used in different reaction tubes. Restriction fragments were generated by KpnI digestion.…”
mentioning
confidence: 99%
“…Their primers were overlapped at numbers 237-258 bases for a sense primer and 257-276 bases for an anti-sense primer from O-gene cDNA and they used a complex reaction mixture and a radioisotope for detection of the PCR product. Yamamoto et al (1990b) and Lee and Chang (1992) reported PCR-RFLP method. This method was used most popularly at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of ABO genotype from peripheral blood leukocytes was first presented by Yamamoto et al (1990b). Several variations were developed by using PCR-RFLP method (Lee and Chang, 1992), allele specific PCR (AS-PCR) method (Ugozzoli and Wallace, 1992), and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) method (Johnson and Hopkinson, 1992). Yamamoto's method was shown to be accurate in these three years.…”
Section: Introductionmentioning
confidence: 99%